Activity on a Li-rich giant: DI Psc revisited. Issue Volume 9:Issue S302(2013) (7th August 2014) - Kriskovics, Levente; Kővári, Zsolt; Vida, Krisztián; Oláh, Katalin
Abstract: We present a new Doppler imaging study for the Li-rich single K-giant DI Psc. Surface temperature maps are reconstructed for two subsequent rotation cycles. From the time evolution of the spot distribution antisolar-type differential rotation pattern is revealed. We show marks of non-uniform Li-abundance as well. The possible connection between the current evolutionary phase of the star and its magnetic activity is briefly discussed.